TATO DAYAK DENGAN APLIKASI BORDIR PADA BAHAN KULIT - Iqbal Lina Rimawati; Salim; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2021)
Indonesia is a country that is famous for its many diverse cultures and from various regions, so there are many Indonesian cultures that are rarely known by many people, even the Indonesian people themselves. The many cultures and languages that exist in Indonesia give this country its own color and also become one of the icons and special attractions for foreigners, the many cultural differences in Indonesia have a positive impact on society.One of Indonesian culture that is not well known is traditional Indonesian tattoos, where tattoos are one of the cultural customs of several tribes in Indonesia, namely the Mentawai, Dayak, and Moi tribes. Tattoos on each tribe are symbols or traditional traditions for them, which have their own meaning. Of the three tribes, the most familiar are Dayak tattoos and Moi tattoos, but the ones that are more widely used by the general public are Dayak tattoo motifs.Keywords: Tattoos are symbols of the Mentawai, Dayak, and Moi traditional traditions